1995
DOI: 10.1002/ccd.1810350208
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary ST‐T alternans during coronary balloon angioplasty

Abstract: To evaluate the presence and clinical significance of electrical alternans during PTCA, intracoronary electrocardiography (ic-ECG) was performed in 65 consecutive lesions. ST-T alternans, defined as a beat-to-beat difference in the ST elevation > or = 1 mm, was present in five lesions (7.7%), all in the proximal left anterior descending (LAD) coronary artery. The phenomenon was seen only after 130 sec (mean 174 +/- 57) of balloon inflation. Only two of the five showed ST-T alternans simultaneously on both surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…ST alternans has been reported only rarely on the surface electrocardiogram during angioplasty, particularly during prolonged inflations.7-9) The current findings were observed by intracoronary electrocardiogram. Intracoronary electrocardiograms are known to be more sensitive than surface recordings,12) and alternans is known to be a localized phenomenon in some cases.15) However, the rarity of ST alternans is suggested by the fact that no cases were observed in 25 patients studied by intracoronary electrocardiogram during angioplasty by Friedman et al,12) 7.7% of intracoronary electrocardiograms by Kwan et al,11) and in 174 patients studied in our laboratory, ST alternans was observed in 5% of intracoronary electrocardiogram recordings. Discrepancies in the ST alternans were usually observed during coronary angioplasty of the circumflex coronary artery at which surface electrocardiograms showed minimal ST changes during balloon inflation.…”
Section: Case Reportmentioning
confidence: 99%
“…ST alternans has been reported only rarely on the surface electrocardiogram during angioplasty, particularly during prolonged inflations.7-9) The current findings were observed by intracoronary electrocardiogram. Intracoronary electrocardiograms are known to be more sensitive than surface recordings,12) and alternans is known to be a localized phenomenon in some cases.15) However, the rarity of ST alternans is suggested by the fact that no cases were observed in 25 patients studied by intracoronary electrocardiogram during angioplasty by Friedman et al,12) 7.7% of intracoronary electrocardiograms by Kwan et al,11) and in 174 patients studied in our laboratory, ST alternans was observed in 5% of intracoronary electrocardiogram recordings. Discrepancies in the ST alternans were usually observed during coronary angioplasty of the circumflex coronary artery at which surface electrocardiograms showed minimal ST changes during balloon inflation.…”
Section: Case Reportmentioning
confidence: 99%
“…T‐wave alternans is an umbrella term referring to alternation of the ECG ST‐segment, T or U wave, and has been shown to be useful in predicting future arrhythmia risk 18 . ST‐alternans occurs during a proportion of coronary angioplasty procedures, and there is modest evidence that the IC‐ECG is more sensitive at detecting ST‐alternans than the S‐ECG 19–21 . ST‐alternans on IC‐ECG was shown to identify a large area of myocardial ischemia, 22 is associated with the occurrence of ventricular arrhythmias during angioplasty, 19 and may be abolished by preconditioning 21 .…”
Section: Morphology Of the Intracoronary Electrocardiogrammentioning
confidence: 99%
“…ST‐alternans occurs during a proportion of coronary angioplasty procedures, and there is modest evidence that the IC‐ECG is more sensitive at detecting ST‐alternans than the S‐ECG 19–21 . ST‐alternans on IC‐ECG was shown to identify a large area of myocardial ischemia, 22 is associated with the occurrence of ventricular arrhythmias during angioplasty, 19 and may be abolished by preconditioning 21 . It is possible that persisting ST‐alternans on IC‐ECG could identify patients with unrecognized ongoing ischemia or patients requiring more intensive postprocedural monitoring.…”
Section: Morphology Of the Intracoronary Electrocardiogrammentioning
confidence: 99%